(untitled) (Fisioterapia e Pesquisa, 2014)
The objective of this study was to analyze the reliability of the intra and inter-evaluators measures, with universal goniometer and fleximeter. Eighty university students (45 women and 35 men [average±SD]; age: 20.81±2.63 years, body mass: 68.36±16.31 kg, height: 1.69±0.09 m, BMI: 23.88±4.15 kg/m2) were submitted to goniometry and fleximetry of elbow and knee flexion, ankle dorsiflexion and wrist extension. It was calculated the intraclass correlation coefficient (ICC), considering a significance level of 5%. Overall, the results showed very strong (ICC: 0.91≤0.99; P